2021
DOI: 10.1021/acs.jctc.0c01199
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Coordinate and Thermodynamics of Base Flipping in RNA

Abstract: Base flipping is a key biophysical event involved in recognition of various ligands by ribonucleic acid (RNA) molecules. However, the mechanism of base flipping in RNA remains poorly understood, in part due to the lack of atomistic details on complex rearrangements in neighboring bases. In this work, we applied transition path sampling (TPS) methods to study base flipping in a double-stranded RNA (dsRNA) molecule that is known to interact with RNA-editing enzymes through this mechanism.We obtained an ensemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In addition, we observed that nucleotide U7 flips inward and points toward the core of the HIV-1 Tar RNA in both the bound B1 and B2 low-energy conformations (Figure 5B,C) and the 1UUD 67 PDB structure, while it flips outward in the unbound U low-energy conformation (Figure 5G). The observation of the nucleotide U7 "base-flipping" 77 phenomenon during ligand binding illustrated the importance of this nucleotide in the ligand binding to the HIV-1 Tar RNA. Furthermore, two slightly different binding pathways of the rbt203 ligand to the HIV-1 Tar RNA could be observed from the free energy profile in Figure 5.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition, we observed that nucleotide U7 flips inward and points toward the core of the HIV-1 Tar RNA in both the bound B1 and B2 low-energy conformations (Figure 5B,C) and the 1UUD 67 PDB structure, while it flips outward in the unbound U low-energy conformation (Figure 5G). The observation of the nucleotide U7 "base-flipping" 77 phenomenon during ligand binding illustrated the importance of this nucleotide in the ligand binding to the HIV-1 Tar RNA. Furthermore, two slightly different binding pathways of the rbt203 ligand to the HIV-1 Tar RNA could be observed from the free energy profile in Figure 5.…”
Section: ■ Discussionmentioning
confidence: 99%
“…If the stable states A and B are separated by a high free energy barrier, an enhanced sampling scheme is often necessary to explore the low probability, rare configurations at the kinetic bottlenecks of the associated transition. , Many studies on enzyme catalyzed chemical reactions employ one or more bias potentials along a set of collective variables (CVs) such as interatomic distances, angles, and dihedral angles that may be chosen empirically or by automated machine learning methods. , An unbiased enhancement in sampling, on the other hand, may be achieved through methods such as transition path sampling (TPS), ,, transition interface sampling (TIS), and their latest variants . These methods involve a Markov chain Monte Carlo in the trajectory space, thereby circumventing the problem of knowing the CVs to be sampled a priori .…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature results have also shown the benefits of incorporating watercoordination-based CVs for obtaining PMFs for the translocation of charged or polar molecules across a lipid bilayer. 43,44 These results indicate that future work should consider the further refinement of current CVs 56,57 and alternative CVs that capture variations in local water density to augment geometric CVs when considering the translocation or flipping of complex molecules such as the peptides studied here.…”
Section: ■ Results and Discussionmentioning
confidence: 85%